Effect of growing media composition on growth, flowering and bulb production of LA hybrid (Red Alert) and Oriental (Avocado) group of Lilium under protected condition - CHAUDHARY, NARENDRA; SINDHU, S S; KUMAR, RAMESH; SAHA, T N; RAJU, D V S; ARORA, AJAY; SHARMA, R R (The Indian Journal of Agricultural Sciences, 2018)
An experiment was carried out to study the effect of growing media on growth, flowering and bulb production of LA hybrid and Oriental group of Lilium under protected condition. One cultivar from each group (Cv. Red Alert from LA hybrid group and cv. Avocado from Oriental group) were selected for the experiment. Fresh and healthy bulbs of each cultivar were planted in the different media composition and placed under protected condition. Results of present study showed that all the vegetative attributes of both the cultivars, viz. number of leaves, leaf area, leaf length, leaf width, plant height and stem diameter found optimistic in media containing cocopeat and vermiculite either with perlite or soil. Flowering traits, viz. number of days from visible bud to flowering, total number of buds, bud diameter, flower bud length, days taken to ¼, ½, ¾ colour bud break and full colour bud development, total number of flowers, diameter of flowers, duration of flowering and vase life of both the cultivar were also reported superior in media containing cocopeat and vermiculite either with perlite or soil. Similarly, bulb attributing charactersviz. number of bulblets, weight of bulb and bulblets, diameter of bulb and bulblets of both the cultivars were also recorded promising in media containing cocopeat and vermiculite either with perlite or soil. It could be concluded that media containing cocopeat and vermiculite either with soil or perlite observed to be the best substrate for growth, flowering and bulb production of Lilium.